Economic evaluation of 2014 cholera outbreak in Ghana: A household cost analysis - Dziedzom Kwesi Awalime; Bernard Bright K. Davies-Teye; Linda A. Vanotoo; Nkechi S. Owoo; Edward Nketiah-Amponsah (Health Economics Review, 2017)
Introduction: Ghana experienced its worst cholera outbreak in three decades in 2014. Evidence of cholera economic costs on affected households has been limited. This study aimed at determining economic costs on households affected by the cholera outbreak in a Coastal Region of Ghana. Methods: Two districts; High and Low Incidence Areas (HIA and LIA) were selected in comparative cost analysis and disease impact on affected households assessed based on scientifically documented economic indicators. A total of 418 (282 HIA and 136 LIA) households that experienced at least one case of cholera infection were interviewed. Direct and indirect costs were estimated. Correlates of household's cholera infection were estimated using Tobit Regression model in STATA 13. Results: Average direct cost to households in HIA amounted to USD 106.88, almost 2 folds higher than LIA (USD 62.02). Potential cost saving of an episode of cholera is USD 99,201.28 in LIA and raises almost 8 folds in HIA (USD 782,611.60). Households in lowest income category had the highest incidence of cholera (0.073) compared to other categories plus other factors were significant in explaining cholera incidence. Conclusions: The study showed considerable differences in HIA and LIA costs with higher household economic impact of cholera on the lowest income category. Results underscore the need for pragmatic policy interventions to avert recurrent outbreaks and emphasis huge potential cost saving with reducing cholera cases.
Keywords: 330; Cholera; HIA; LIA; Cost of illness; Household; Ghana